The Effectiveness of Project-Based Writing Toward Students’ Mastery of Grammatical Accuracy - Nurcahyoko, Kunto; Maiza, Masfa; setiawan, Antonius (Journal of English Language Teaching and Islamic Integration (JELTII), 2019)
Teaching grammar has been one of the most challenging issues in Indonesia. Teacher-centered approach and the lack of students‟ motivation are among the factors limiting students to master grammar. The study aims at investigating the effectiveness of project-based writing toward students‟ mastery of grammar based on their motivation level. The study used a 2X2 factorial research design involving 60 students in two groups in one of high schools in Landak Regency, West Kalimantan. The data were collected through test and questionnaires. SPSS 20 was used for analyzing the data. The finding reveals that project-based writing is effective toward students‟ mastery of grammar. Besides, motivation level is also effective toward students‟ grammatical accuracy. Lastly, the analysis of variance shows that there is no interaction among students‟ motivation, techniques, and students‟ grammar with the level of sig. value at 0.821. The study suggests that teachers must be able to consider the presence of both a project and motivation in teaching and learning, especially to teach grammatical accuracy.